Alcune considerazioni psicanalitiche sull’anoressia - Zangari, Cinzia (Metapsychologica - rivista di psicanalisi freudiana, 2023)
Over the past 50 years, anorexia has been the center of several studies the aim of which is not only to investigate the underlying causes, but also to find a therapeutic method capable of overcoming the powerful resistances that patients oppose to treatment. During their research, most researchers have increasingly drifted away from the psychoanalytic theoretical foundations, considering them to be inadequate and reductive. Through this article, the author will give evidence of how a return to Freud’s original thought, and to the sexual etiology of eating disorders, leads to a profoundly explanatory theoretical response to a complex phenomenon such as anorexia.